2016
DOI: 10.18632/oncotarget.13408
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor activity of the combination of salubrinal and rapamycin against human cholangiocarcinoma cells

Abstract: Less is known about the roles of eukaryotic initiation factor alpha (eIF2α) in cholangiocarcinoma (CCA). Here, we report that eIF2α inhibitor salubrinal inhibits the proliferation of human CCA cells. Clinical application of mammalian target of rapamycin (mTOR) inhibitors only has moderate antitumor efficacy. Therefore, combination approaches may be required for effective clinical use of mTOR inhibitors. Here, we investigated the efficacy of the combination of salubrinal and rapamycin in the treatment of CCA. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…It has been reported that the inactivation of mammalian target of rapamycin (mTOR) is implicated in cell contact inhibition (24). We have previously reported that the mTOR pathway plays an important role in CCA cell growth and survival (25). Here we wonder whether there is a link between c-Myc and mTOR in contact inhibition regulation in CCA cells.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been reported that the inactivation of mammalian target of rapamycin (mTOR) is implicated in cell contact inhibition (24). We have previously reported that the mTOR pathway plays an important role in CCA cell growth and survival (25). Here we wonder whether there is a link between c-Myc and mTOR in contact inhibition regulation in CCA cells.…”
Section: Resultsmentioning
confidence: 92%
“…Consistently, our data show that the activity of mTOR decreased obviously in contact-inhibited normal biliary epithelial cells. We and others have previously found that the mTOR pathway is implicated in the carcinogenesis and progression of CCA and mTOR inhibition suppresses the growth of human CCA cells (25,32). Whether the implication of mTOR in CCA is associated with contact inhibition regulation has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Sal is a drug that impairs eIF2α dephosphorylation (42). Studies have reported that Sal increased sensitivity of cancer cell and xenograft tumor models to chemotherapy or rapamycin (28,43,44). 4E1RCat was identified as a molecule capable of impairing eIF4 assembly (20).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of Sal to 4E1RCat for experimentation was based on the published literature. Specifically, Sal at 1 mg/kg has been used by multiple groups for its ability to inhibit tumor xenografts (28) and other pharmacological activities (29)(30)(31). However, 4E1RCat was not well-studied in mouse models, and hence, the dose of Sal was fixed and 4E1RCat varied to assess and maximize the combined effect.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Salubrinal, a phosphatase inhibitor that represses eIF2α dephosphorylation , is currently in clinical trials in combination with carfilzomib for patients with multiple myeloma (NCT01775553). Further, salubrinal in combination with the mTOR inhibitor rapamycin shows enhanced anti‐tumour activity against cholangiocarcinoma cells . On the other side of the coin, ISRIB (integrated stress response inhibitor) is a small molecule inhibitor identified by cell‐based small molecule screens.…”
Section: Targeting the Translational Machinery In Cancermentioning
confidence: 99%